Application of Al-Ijarah Al-Maushufah Fi Al-Dzimmah for Infrastructure Project Financing in Indonesia - Rega Felix; Lastuti Abubakar (Universitas Airlangga, 2019)
Islamic bank has a huge potential to involve in large project financing such as infrastructure. The demand for infrastructure provision in Indonesia is growing rapidly, so the Islamic bank should become one of the financial institutions for a financing infrastructure project. One of the products of Islamic bank is lease based contract or ijarah. In 2016, the Indonesian Islamic Scholars Council (MUI) enacted Fatwa that allowed ijarah contract for a forward obligation or called al-ijarah al-maushufah fi al-dzimmah (IMFD). IMFD has some characteristics that equitable for infrastructure project needs, such as for long term financing. The main issues in this research are to drawn a model for infrastructure project financing by applying IMFD and observe the readiness of Indonesian regulation to support the implementation of IMFD on infrastructure project financing. The type of research is the normative study, and the approach of this research having four methods approach among others are statute approach, conceptual approach, cases approach, and comparative approach. The results of this research are model for infrastructure project financing by applying IMFD is by combining musharakah-istishna’-ijarah (IMFD) and regulation in Indonesia is not ready enough to support the implementation of IMFD on infrastructure project financing because combination of three contracts like musharakah-istishna’-IMFD, implementation of liquidated damages in istishna’ contract, and allowance IMFD in infrastructure project are not regulated in Indonesia.